DEVELOPING ENGLISH COMPETENCES IN THE TOURISM SECTOR THROUGH ESP (ENGLISH FOR SPECIFIC PURPOSES) COURSES - Ibragimova , Dilnoza (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
Tourism is one of the fastest growing sectors of the global economy, requiring professionals to possess strong communication skills in English. As English has become the dominant language of international tourism, employees must be equipped with specialized competences that go beyond general language proficiency. English for Specific Purposes (ESP) courses provide a targeted approach to language learning by focusing on professional contexts and industry-specific needs. This paper explores the role of ESP in developing essential English competences among tourism students and professionals. The study reviews key teaching strategies such as role-plays, simulations, task-based learning, and the use of authentic materials. Findings reveal that ESP courses significantly enhance linguistic skills, communicative competence, intercultural awareness, and professional readiness. Despite certain challenges, including diverse learner needs and the shortage of qualified ESP instructors, the overall benefits are evident. The paper concludes that ESP should be considered an indispensable component of tourism education, equipping learners with both language proficiency and industry-specific skills required for global competitiveness.